QTL analysis for cooking traits of super rice with a high‐density SNP genetic map and fine mapping of a novel boiled grain length locus. Issue 5 (13th August 2015) - Li, Yuanyuan; Tao, Hongjian; Xu, Jie; Shi, Zhenyuan; Ye, Weijun; Wu, Liwen; Zeng, Dali; Gao, Zhenyu; Guo, Longbiao; Yuanyuan, Li
Abstract Hybrid rice has contributed substantially to the improvement of grain production worldwide, yet its poor cooking and tasting characteristics have long been recognized. In this study, 132 recombinant inbred lines derived from LYPJ were used to identify quantitative trait loci (QTLs) for 12 cooking traits with the high‐density SNP linkage map recently developed by our team. We identified 17 QTLs on chromosomes 1, 2, 4, 5, 6, 7, 8, 9 and 11, which accounted for 7.50% to 23.50% of the phenotypic variations. A novel major QTL qBGL7 for boiled grain length was further fine‐mapped to an interval of 440 Kb between the two markers RM21906 and gl3 using a BC3F2 population. Two near‐isogenic lines with extreme boiled grain length, GX5‐176 and GX5‐101, could be directly used in improving cooking quality. We also identified a QTL for soaked grain width expansion rate, qSGWE6, in the Wx gene region on chromosome 6. The Wx differential regulation coincided with sequential variation between the two parents. Our work offered a theoretical basis for molecular breeding of high‐quality hybrid rice.